Türkiye'de ve Dünyada Yiyecek İçecek Sektörüne Yönelik Eğitim Veren Lisans Programlarının Kıyaslanması - Çarbuğa, Ümit; Memiş Kocaman, Emel (Muş Alparslan Üniversitesi, 2019)
In this study; it has beenaimed that identifying the names of undergraduate programmes which trainoriented to food and beverage sector in Turkey and in the world and theirmutual and different sides in regards to the faculty/college which they arewithin. For this purpose, all of the universities in Turkey has been scanned.From 8 countries abroad, (Spain, Italy, England, USA, Switzerland, Sweden)websites of randomly selected 149 universities has been examined. It has beenseen that, 82.0% of 50 programmes which train oriented to food and beveragesector in Turkey bear the name of “gastronomy and culinary arts”. It has beenseen that 38.0% of the programmes are within the tourism faculties. In 6 of thecountries that are aboard taken in the scope of the research,   it has been detected that there are relatedundergraduate programmes. It has been detected that programme names are“culinary arts” and “gastronomical science” at furthest, in the universitieswhere there are related programmes. As a result of research findings it can besaid that there is a significant variety in terms of the programmes names andfaculty and colleges which the programmes are within.

Bu çalışmada; Türkiye’de vedünyada yiyecek içecek sektörüne yönelik eğitim veren lisans programlarınınisimleri ve bünyesinde bulundukları fakülte/yüksekokul bakımından ortak vefarklı yönlerinin tespit edilmesi amaçlanmıştır. Bu amaçla, Türkiye’deki üniversitelerintamamı taranmıştır. Yurtdışından 8 ülkede (İspanya, İtalya, İngiltere, ABD, İsviçre, İsveç, Japonya ve Avustralya) rastgele seçilen 149 üniversitenin websiteleri incelenmiştir. Türkiye’de yiyecek içecek sektörüne yönelik lisanseğitimi veren 50 programdan %82.0’ının “gastronomi ve mutfak sanatları” isminitaşıdığı belirlenmiştir. Programlardan %38.0’ının turizm fakülteleri bünyesindebulundukları görülmüştür. Yurtdışında araştırma kapsamına alınan ülkelerden6’sında ilgili lisans programları tespit edilmiştir. İlgili programlarınbulunduğu üniversitelerde program isimlerinin; en fazla “mutfak sanatları” ile“gastronomik bilimler” olduğu tespit edilmiştir. Türkiye’de ve diğer ülkelerdebu alanda eğitim veren programlar ile bünyesinde bulunduklarıfakülte/yüksekokulların geniş bir isim çeşitliliğine sahip olduğu sonucunavarılmıştır.
The Comparison of Undergraduate Programmes Which Train Oriented to Food and Beverage Sector in Turkey and the World
anemon
Keywords: Gastronomy; Food and beverage; Education; Vocational education; Gastronomi; yiyecek ve içecek; eğitim; mesleki eğitim